2003
DOI: 10.1016/s1535-6108(03)00108-9
|View full text |Cite
|
Sign up to set email alerts
|

PKC412 overcomes resistance to imatinib in a murine model of FIP1L1-PDGFRα-induced myeloproliferative disease

Abstract: FIP1L1-PDGFRalpha causes hypereosinophilic syndrome (HES) and is inhibited by the tyrosine kinase inhibitor imatinib (Gleevec). Imatinib is a potent inhibitor of ABL, ARG, PDGFRalpha, PDGFRbeta, and KIT and induces durable hematologic responses in HES patients. However, we observed relapse with resistance to imatinib as consequence of a T674I mutation in FIP1L1-PDGFRalpha, analogous to the imatinib-resistant T315I mutation in BCR-ABL. We developed a murine bone marrow transplant model of FIP1L1-PDGFRalpha-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
175
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(188 citation statements)
references
References 39 publications
12
175
0
1
Order By: Relevance
“…PKC412 has previously been shown to be an effective inhibitor of the imatinib-resistant c-KIT mutant, D816V, which is associated with systemic mast cell disease14 , 15. PKC412 has also been shown to be effective against the FIP1L1-PDGFRA kinase associated with hypereosinophilic syndrome and chronic eosinophilic leukemia 16 , and can override imatinib resistance occurring in point mutated FIP1L1-PDGFRA-induced myeloproliferative disease 17 . In addition, GIST patient samples positive for the imatinib resistant mutant c-KIT or PDGFRA were found to respond well to PKC412 8 .…”
Section: Discussionmentioning
confidence: 99%
“…PKC412 has previously been shown to be an effective inhibitor of the imatinib-resistant c-KIT mutant, D816V, which is associated with systemic mast cell disease14 , 15. PKC412 has also been shown to be effective against the FIP1L1-PDGFRA kinase associated with hypereosinophilic syndrome and chronic eosinophilic leukemia 16 , and can override imatinib resistance occurring in point mutated FIP1L1-PDGFRA-induced myeloproliferative disease 17 . In addition, GIST patient samples positive for the imatinib resistant mutant c-KIT or PDGFRA were found to respond well to PKC412 8 .…”
Section: Discussionmentioning
confidence: 99%
“…PKC412, a potent FLT3 inhibitor that is in clinical development for the treatment of AML, was the first inhibitor to be identified with activity against the FIP1L1-PDGFRa T674I mutant. 65 Using both in vitro and in vivo mouse models, we demonstrated the ability of PKC412 to induce apoptosis in FIP1L1-PDGFRa T674I-transformed cells, and to significantly reduce leukocytosis and splenomegaly in a FIP1L1-PDGFRa T674I mouse model. 65 In a second study, we identified sorafenib, a BRAF and VEGFR inhibitor approved for the treatment of renal cell carcinoma, as another potent inhibitor of both FIP1L1-PDGFRa and the T674I mutant form.…”
Section: Spotlightmentioning
confidence: 90%
“…65 Using both in vitro and in vivo mouse models, we demonstrated the ability of PKC412 to induce apoptosis in FIP1L1-PDGFRa T674I-transformed cells, and to significantly reduce leukocytosis and splenomegaly in a FIP1L1-PDGFRa T674I mouse model. 65 In a second study, we identified sorafenib, a BRAF and VEGFR inhibitor approved for the treatment of renal cell carcinoma, as another potent inhibitor of both FIP1L1-PDGFRa and the T674I mutant form. 89 In addition, nilotinib was also shown to have some activity towards both FIP1L1-PDGFRa and the T674I mutant.…”
Section: Spotlightmentioning
confidence: 90%
See 2 more Smart Citations